A Deeper Look into the Role of Political Institutions on Economic Growth: Evidence from ASEAN Countries - Kharisma, Bayu; Wardhana, Adhitya; Gunadi, Tiara Pangestika (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2025)
The occurrence of wars, ethnic conflicts, general elections, and coups in Southeast Asian countries has led to a reduction in institutional quality, resulting in a deteriorating economic situation. Since the 1998 monetary crisis, the institutional quality in the Southeast Asian region has been inconsistent, decreasing the region's appeal to foreign investors. Optimal political stability can foster favourable circumstances for investors, hence stimulating a nation's economic expansion. This study examines the impact of political institution on economic growth on a panel of ASEAN countries, including Indonesia, Malaysia, Singapore, Thailand, the Philippines, Brunei Darussalam, Vietnam, Laos, Myanmar, and Cambodia from 2010 to 2021. The data used for this analysis was obtained from the World Bank, and the Fixed Effect Model (FEM) was employed. The study findings indicate that political institutions favour and substantially impact economic growth. These results suggest that political institutions have a significant impact on sustaining a country's economic development.